Acute Ischemic Stroke Associated with Myocardial Infarction: Challenges and Management - Boyanpally, Anusha; Cutting, Shawna; Furie, Karen (Seminars in Neurology, 2021)
Acute ischemic stroke (AIS) and acute myocardial infarction (AMI) may co-occur simultaneously or in close temporal succession, with occurrence of one ischemic vascular event increasing a patient's risk for the other. Both employ time-sensitive treatments, and both benefit from expert consultation. Patients are at increased risk of stroke for up to 3 months following AMI, and aggressive treatment of AMI, including use of reperfusion therapy, decreases the risk of AIS. For patients presenting with AIS in the setting of a recent MI, treatment with alteplase, an intravenous tissue plasminogen activator, can be given, provided anterior wall myocardial involvement has been carefully evaluated. It is important for clinicians to recognize that troponin elevations can occur in the setting of AIS as well as other clinical scenarios and that this may have implications for short- and long-term mortality.
Keywords: ischemic stroke; acute myocardial infarction; thrombolytic therapy; cerebral infarction; tissue plasminogen activator; percutaneous coronary intervention